How Leadership Failures Fuel Covetousness and Corruption in Nigeria's Educational System? - Adeoye, Moses Adeleke; Oladimeji, Rasheedat Modupe; Akinnubi, Olaolu Paul (Universitas Pendidikan Ganesha, 2023)
The importance of integrity is undermined in communities where corruption is pervasive and the respect for authority figures is diminished. This research paper aims to analyze how leadership failures contribute to covetousness and corruption within Nigeria's educational system. The study analyzes the impact of ineffective leadership on the prevalence of unethical practices, such as bribery, embezzlement and favoritism. Data sources included academic literature, reports and official documents. Then data is analysis and extracted from selected literature. Through an analysis of relevant literature and case studies, the research highlights the detrimental consequences of these corrupt practices on the quality of education and the overall development of the country. In conclusion, strengthening legal and regulatory frameworks, enhancing oversight mechanisms, investing in capacity building and promoting a culture of integrity are key recommendations that can help pave the way for a more transparent, accountable and effective educational system. By implementing these recommendations, Nigeria can ensure that its educational institutions are led by individuals who prioritize the well-being and future of the nation's students.